Multilayered Sociocultural Phenomena: Associations Between Subjective Well-Being and Economic Status - Fukushima, Shintarō (Zygon, 2016)
In this article, incoherent results of the associations between subjective well-being and economic status at multiple social levels are shown. Although individual-level positive associations are shown within developed countries, national-level associations disappear among developed countries. Group/area-level associations, meanwhile, do exist within Japanese societies. From these inconsistent phenomena, a sociocultural unit is proposed, within which well-being of people is collectively shared based on mutual reciprocity. The simple addition of social scientific results themselves cannot reconstruct the whole range of phenomena. Humanities could be considered as the glue, which adds sociocultural meanings to the generalized scientific results.